Phosphorus extraction from fish waste bones ash by acidic leaching method - Darwish, Mohamad; Aris, Azmi; Puteh, Mohd Hafiz; Abdul Kadir, Aeslina; Mohamed Najib, Mohamed Zuhaili; Mustafa, Shaymaa (IOS Press, 2020)
The worldwide demand of phosphorus (P) is rising rapidly; however phosphate ores are not renewable. Fish bones contain high amounts of P, but hardly recycled or reused. Therefore, this study investigated P extraction from fish waste bones by acidic leaching method. The study shows that P content in fish bones ash is around 17 wt.%. Acidic leaching of P is carried out using different concentrations of sulphuric acid (H2SO4), to determine the optimum condition of P recovery. More than 97% of P is extracted using 2 M H2SO4 and an acid-ash ratio of 1.5 kg H2SO4/kg ash. Besides, it was found that a reaction period of 90 min is enough to accomplish complete dissolution of fish waste bones ash. The present work suggested that recovering P from fish bones ash is worthy, which is highly advantageous for further applications that apply P additions.